ACCOUNTING AND ECONOMIC ANALYSIS: AN INTEGRATED APPROACH TO CALCULATING FINANCIAL INDICATORS (Modern education and development, 2025)
This article explores the topic “Accounting and economic analysis: an integrated approach to calculating financial indicators”. The article analyzes the relationship between accounting and economic analysis, as well as their importance in the process of calculating financial indicators. Accounting can clearly indicate the financial condition of the enterprise, and economic analysis can help with in-depth analysis of this information and strategic decision-making. Through this integrated approach, more efficient and reliable results can be achieved in the calculation of financial indicators.